Non-invasive prenatal testing is not a substitute for first trimester ultrasound screening (Swiss Medical Weekly, 2025)
The ultrasound examination in the first trimester is a crucial tool in prenatal diagnostics. Its primary aim is the early detection of fetal structural anomalies with the option to assess the risk for the common fetal trisomies (in Switzerland: “Ersttrimestertest”). The latter is achieved by combining ultrasound data with biochemical blood tests.In addition to chromosomal diagnostics, the first-trimester ultrasound plays an essential role in evaluating pregnancy risks as well as the overall health of the fetus. This method is non-invasive, safe and effective, offering invaluable information to both healthcare professionals and expectant parents that is critical for further pregnancy care.The introduction and wide-spread use of another, molecular test, NIPT (“non-invasive prenatal testing”) should be seen as a useful additional option to, not a substitute for first trimester ultrasound. NIPT has high detection rates for “the common trisomies”, but, in isolation, is insufficient for comprehensive early fetal assessment.